Analisa SWOT dalam Bisnis Pariwisata Tour Travel “Eagle Tour and Travel“ - Agus Setiadi (Syntax Idea)
Alongside the growth of the tourism industry, especially in the city of Batu, tour & travel businesses such as Eagle Tour & Travel play a crucial role in providing comprehensive and organized travel services for tourists. However, despite having good prospects, businesses like Eagle Tour & Travel still face various operational and marketing challenges. This research is developed to elaborate on the strengths, weaknesses, opportunities, and threats (SWOT) related to the Eagle Tour and Travel business established since 2015. This study aims to conduct a SWOT analysis of the tour and travel tourism business, focusing on the Eagle Tour and Travel brand in Batu City, East Java. Using a qualitative descriptive approach and SWOT analysis method focused on obtaining effective promotional and sales enhancement strategies based on recommendations following external environmental indicators (External Factor Analysis Strategy), then strengths and weaknesses are obtained through internal factors IFAS (Internal Factor Analysis Strategy). The results of the study enable business practitioners to take strategic steps that align with the quadrants of the SWOT Analysis. The combination of various strategies above will assist Tour Travel companies in enhancing competitiveness, facing challenges, and winning the competition in the tourism industry